1987
DOI: 10.1038/clpt.1987.49
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and cerebrospinal fluid pharmacokinetics of 3′-azido-3′-deoxythymidine: A Novel pyrimidine analog with potential application for the treatment of patients with AIDS and related diseases

Abstract: We investigated the clinical pharmacokinetics of azidothymidine (N3TdR) as part of a phase I/II trial in the treatment of acquired immunodeficiency syndrome and related diseases. During the 6-week course of therapy, drug levels in plasma, cerebrospinal fluid, and urine were determined by HLPC. The plasma half-life of N3TdR was 1.1 hour. The total body clearance was 1.3 L/kg/hr. At intravenous doses of 5 mg/kg or oral doses of 10 mg/kg, plasma levels were continuously maintained above the target level of 1 mumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
0
6

Year Published

1988
1988
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 370 publications
(181 citation statements)
references
References 0 publications
9
166
0
6
Order By: Relevance
“…Zeta potential of formulation was -6.74s mv which showed that the higher concentration of ethanol make the negative charge on vesicles surface. These result further supported by the observation of methotrexate (MTX) loaded ethosome made by Dubey et al [7,8]. Though with increase in ethanol concentration the vesicular size decreased, a phenomenon observed by number of scientific groups.…”
Section: Figure 5 Percent Entrapment Of A) Ethanol Concentration B) supporting
confidence: 73%
See 1 more Smart Citation
“…Zeta potential of formulation was -6.74s mv which showed that the higher concentration of ethanol make the negative charge on vesicles surface. These result further supported by the observation of methotrexate (MTX) loaded ethosome made by Dubey et al [7,8]. Though with increase in ethanol concentration the vesicular size decreased, a phenomenon observed by number of scientific groups.…”
Section: Figure 5 Percent Entrapment Of A) Ethanol Concentration B) supporting
confidence: 73%
“…When ethosomal carriers, which contain ethanol, and soft small vesicles are applied to the skin a number of concomitant processes may take place, involving the stratum corneum and pilosebaceous pathway. Evidence of existence of the follicular transport pathway taken by the lipid vesicles have been reported [7][8][9][10][11][12][13][14][15][16][17]. first, ethanol disturbs the organization of the stratum corneum lipid bilayer and enhances its lipid fluidity.…”
Section: Figure 7 In Vitro Release Of Aceclofenac From Mouse Skinmentioning
confidence: 99%
“…In addition to mutations previously associated with zidovudine resistance, three sequences contained the mutation 215 ~hr~Asp, the phenotype of which is unknown. Zidovudine sensitive genotypes persisted in the brain of this patient, and this might suggest that zidovudine did not reach inhibitory concentrations within this organ due to restricted transport across the blood brain barrier or from the cerebro-spinal fluid to the brain (Klecker et al, 1987;Terasaki & Pardridge, 1988;Lupia et al, 1993). The presence of zidovudine resistant genotypes in the cerebro-spinal fluid has been reported (di Stefano et al, 1993), although at present it is not clear whether this population is representative of that found in the brain.…”
Section: Analyses Of R T Coding Regionsmentioning
confidence: 79%
“…The main clinical limitations to the therapeutic effectiveness of AZT are its short plasma half-life (approximately 1 h), necessitating frequent administration of large doses to maintain therapeutic drug levels, and its dose-dependent toxicities. [1][2][3][4] In fact, after oral administration, AZT is completely and rapidly absorbed leading to very high initial plasma concentrations and, therefore, a high incidence of toxicity results in frequently occurring side effects. As a result, adequate delivery systems for AZT are still investigated to develop a method to maintain effective plasma concentrations as well as to reduce dose and dose-dependent toxicity.…”
Section: Introductionmentioning
confidence: 99%